Optical Glass and Optical Elements
A tailored glass composition with controlled components achieves low glass transition temperature and optimal optical properties, addressing the limitations of existing glasses for precision pressing and optical elements.
Patent Information
- Application Number
- JP2023092926
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-06-06
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2043-06-06
AI Technical Summary
Existing optical glasses do not effectively balance refractive index, Abbe number, and glass transition temperature, limiting their suitability for precision pressing and other optical applications.
A specific glass composition with controlled amounts of Li2O, B2O3, SiO2, La2O3, ZnO, and TiO2, along with defined ratios, ensures a low glass transition temperature while maintaining desired optical constants, adhering to formulas Tg-88.355*nd+201 and νd>-88.355*nd+201.
The glass composition achieves low glass transition temperatures suitable for precision pressing, while providing high refractive index and low dispersion, enhancing the suitability of optical elements for various applications.
Smart Images

Figure 0007617976000041 
Figure 0007617976000001 
Figure 0007617976000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical glass and an optical element. [Background technology]
[0002] In recent years, various optical glasses have been proposed as materials for optical elements (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-201661 A Summary of the Invention [Problem to be solved by the invention]
[0004] Optical glass in which the refractive index and Abbe number satisfy a certain relational expression is useful as a material for optical elements. For example, a specific example of such a relational expression is "Equation (2): νd>-88.355*nd+201."
[0005] One of the properties desired for optical glass is a low glass transition temperature Tg. Low Tg glass is preferable because it has excellent suitability for precision pressing, for example.
[0006] An object of one aspect of the present invention is to provide an optical glass whose refractive index and Abbe number satisfy the above formula (2) and which has a low glass transition temperature. [Means for solving the problem]
[0007] One aspect of the present invention is In the glass composition expressed in mass%, Li 2 O content exceeds 0% by mass, B 2 O 3 The content is 3.00% by mass or more and 30.00% by mass or less, SiO 2 The content is more than 0% by mass and 8.00% by mass or less, La 2 O 3 The content is 15.00% by mass or more and 55.00% by mass or less, ZnO content is 3.00% by mass or more and 30.00% by mass or less, TiO 2 Content is 0.60% by mass or less, Li 2 The total content of O and ZnO (Li 2 O + ZnO) is 10.20 mass% or more, Li 2 B relative to O content 2 O 3 Mass ratio of content (B 2 O 3 / Li 2 O) is between 5.00 and 21.00, Li 2 SiO vs. O content 2 Mass ratio of content (SiO 2 / Li 2 O) is 10.00 or less, and Glass transition temperature Tg is less than 610℃, Liquidus temperature LT is 1090℃ or higher, The present invention relates to an optical glass in which the refractive index nd and the glass transition temperature Tg satisfy the following formula (1), and the refractive index nd and the Abbe number vd satisfy the following formula (2). Formula (1): Tg<2500*nd-4050 Formula (2): νd>-88.355*nd+201 Effect of the Invention
[0008] According to one aspect of the present invention, it is possible to provide an optical glass having a low glass transition temperature and optical constants useful as a material for optical elements, and also to provide an optical element made of such an optical glass. [Brief description of the drawings]
[0009] [Figure 1]1 shows a schematic cross-sectional view of a precision press molding device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Optical glass] In the present invention and this specification, the glass composition of the optical glass is expressed in mass %, cation % or mole %.
[0011] In the glass composition expressed in mass % and the glass composition expressed in mol %, the glass composition is expressed as a glass composition based on oxides. Here, "glass composition based on oxides" refers to a glass composition obtained by converting the glass raw materials into oxides present in the glass after they are all decomposed during melting. In the glass composition expressed in mass %, the glass composition is expressed on a mass basis (mass %, mass ratio). Hereinafter, for glass compositions expressed in mass %, "mass %" will also be simply written as "%". In the glass composition expressed in mol %, the glass composition is expressed on a molar basis (mol %, molar ratio). Hereinafter, for glass compositions expressed in mol %, "mol %" will also be simply written as "%".
[0012] For glass compositions expressed in cation %, the content and total content of cationic components are expressed in cation %. Here, "cation %" is a value calculated by "(number of cations of interest / total number of cations in glass components) x 100", and means the molar percentage of the amount of cation of interest relative to the total amount of cationic components. Hereinafter, for glass compositions expressed in cation %, "cation %" will also be simply referred to as "%". The cationic ratio is the molar ratio of the contents of cationic components to each other and is equal to the ratio of the contents, expressed as cationic %, of the cationic components of interest. For the cationic component, for example, Li + , Si 4+ However, the valence of the cationic component (e.g., Li + The valence of is +1, Si 4+ The valence of Li is +4) is a value established by convention, and Li, Si, etc. are calculated based on the oxide 2 O, SiO 2This is the same as writing A on an oxide basis. m O n (A represents a cation, O represents oxygen, and m and n are stoichiometric integers.) For a component represented as s+ Here, s = 2n / m. Therefore, for example, when analyzing and quantifying the glass composition, it is not necessary to analyze the valence of the cationic components.
[0013] In the present invention and this specification, the content of a component is 0%, 0.0% or 0.00%, or is not included or not introduced, means that the component is substantially not included, and the content of the component is equal to or less than the impurity level. The content of the component is equal to or less than the impurity level, for example, less than 0.01%. "0%" can mean, for example, "0.0%" or "0.00%".
[0014] The glass composition of the present invention and this specification can be determined by a method such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed for each element using ICP-AES. The analytical values are then converted into oxide notation. The analytical values obtained by ICP-AES may contain a measurement error of, for example, about ±5% of the analytical value. Therefore, the oxide notation values converted from the analytical values may also contain an error of about ±5%.
[0015] The composition expressed in mass % on an oxide basis as a result of quantitative analysis of the glass composition can be converted to a glass composition expressed in cation % by, for example, the following method. If the glass contains N kinds of glass components, the kth glass component is A(k). m O n Here, k is an arbitrary integer between 1 and N. A(k) is a cation, O is oxygen, and m and n are stoichiometric integers. For example, the oxide-based notation is B 2 O3 In the case of m=2, n=3, and SiO 2 In this case, m=1 and n=2. Next, A(k) m O n The content of A(k) is X(k) [mass%]. Here, if the atomic weight of A(k) is P(k) and the atomic number of oxygen O is Q, then A(k) m O n The formal molecular weight R(k) of R(k) = P(k) x m + Q x n It becomes. Furthermore, B = 100 / {Σ[m×X(k) / R(k)]} Then, the cationic component A(k) s+ The content (cation %) of is [X(k) / R(k)]×m×B(cation %). Here, Σ means the sum of m×X(k) / R(K) for k=1 to N. m changes depending on k. s is 2n / m. The molecular weight R(k) may be calculated by rounding off the fourth decimal place and displaying the value to the third decimal place. The molecular weights of some glass components and additives expressed on an oxide basis are shown in Table 1 below.
[0016] [Table 1]
[0017] In the present invention and this specification, the refractive index refers to the refractive index nd at the d line of helium (wavelength 587.56 nm).
[0018] In the present invention and this specification, the Abbe number νd is used as a value indicating a property related to dispersion, and is expressed by the following formula. νd=(nd-1) / (nF-nC) In the above formula, nF is the refractive index at the F line of blue hydrogen (wavelength 486.13 nm), and nC is the refractive index at the C line of red hydrogen (656.27 nm).
[0019] The optical glass (sometimes simply referred to as "glass") will be described in more detail below.
[0020] <Glass composition> (Li 2 O, Li + ) Li (in the glass composition shown in mass% or mole% 2 O, Li in the glass composition shown in cation percentage + ) is a component capable of lowering the glass transition temperature while suppressing a decrease in the refractive index, and therefore its inclusion in the above optical glass is essential.
[0021] In the glass composition shown in mass%, Li 2 The O content is more than 0% and is preferably 0.20% or more, and is more preferably 0.30% or more, 0.40% or more, 0.45% or more, 0.50% or more, 0.55% or more, 0.60% or more, 0.62% or more, 0.64% or more, 0.66% or more, 0.68% or more, 0.70% or more, 0.72% or more, 0.74% or more, 0.76% or more, 0.77% or more, 0.78% or more, 0.79% or more, 0.80% or more, 0.81% or more, 0.82% or more, and 0.83% or more in that order. Li 2 The upper limit of the O content is not particularly limited, and can be, for example, 1.80% or less, preferably 1.70% or less, and more preferably 1.60% or less, 1.55% or less, 1.50% or less, 1.48% or less, 1.46% or less, 1.44% or less, 1.42% or less, 1.40% or less, 1.38% or less, 1.36% or less, 1.34% or less, 1.32% or less, and 1.31% or less, in that order.
[0022] In the glass composition shown in cation percentage, Li + The content is more than 0% and is preferably 0.50% or more, and more preferably in the order of 1.00% or more, 1.50% or more, 2.00% or more, 2.50% or more, 3.00% or more, 3.25% or more, 3.50% or more, 3.75% or more, 4.00% or more, 4.25% or more, 4.50% or more, 4.75% or more, and 5.00% or more. Li+ The upper limit of the content is not particularly limited, and can be, for example, 12.00% or less, preferably 11.00% or less, and more preferably 10.50% or less, 10.00% or less, 9.75% or less, 9.50% or less, 9.25% or less, 9.00% or less, 8.75% or less, 8.50% or less, 8.25% or less, and 8.00% or less, in that order.
[0023] In the glass composition shown in mole percent, Li 2 The O content is more than 0% and is preferably 0.50% or more, and more preferably 1.00% or more, 1.50% or more, 2.00% or more, 2.50% or more, 3.00% or more, 3.10% or more, 3.30% or more, 3.50% or more, 3.70% or more, and 3.91% or more in that order. Li 2 The upper limit of the O content is not particularly limited and can be, for example, 11.00% or less, preferably 10.00% or less, and more preferably 9.50% or less, 9.00% or less, 8.50% or less, 8.00% or less, 7.50% or less, 7.30% or less, 7.10% or less, 6.90% or less, 6.70% or less, and 6.51% or less, in that order.
[0024] (B 2 O 3 ) B 2 O 3 is a network former and is a component that contributes to maintaining the thermal stability and meltability of glass. Therefore, in the glass composition expressed in mass%, B 2 O 3 The content is 3.00% or more, preferably 5.00% or more, and more preferably 6.00% or more, 7.00% or more, 8.00% or more, 8.50% or more, 9.00% or more, 9.50% or more, 10.00% or more, 10.50% or more, and 10.83% or more in that order. B 2 O 3 is also a component that lowers the refractive index of glass when contained in a large amount. Therefore, in the glass composition expressed in mass%, B 2 O 3The content is 30.00% or less, preferably 29.00% or less, and more preferably in the order of 28.00% or less, 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.00% or less, 22.00% or less, 21.00% or less, 20.00% or less, 19.00% or less, 18.00% or less, 17.00% or less, 16.00% or less, 15.50% or less, 15.00% or less, 14.50% or less, 14.00% or less, and 13.78% or less.
[0025] (SiO 2 ) SiO 2 Also, SiO is a network former and is a component that contributes to maintaining the thermal stability and meltability of glass. From this point of view, in the glass composition expressed in mass%, 2 The content is more than 0% and is preferably 0.50% or more, and more preferably in the order of 1.00% or more, 1.50% or more, 2.00% or more, 2.25% or more, 2.50% or more, 2.75% or more, 2.80% or more, 2.85% or more, 2.90% or more, 2.95% or more, 3.00% or more, 3.02% or more, 3.04% or more, and 3.06% or more. SiO 2 However, when contained in large amounts, it is also a component that lowers the refractive index of the glass. Therefore, in the glass composition expressed in mass%, SiO 2 The content is 8.00% or less, preferably 7.50% or less, more preferably 7.00% or less, and more preferably 6.75% or less, 6.50% or less, 6.25% or less, 6.00% or less, 5.75% or less, and 5.60% or less in that order.
[0026] (B 2 O 3 / Li 2 O) In the glass composition shown in mass%, Li 2 B relative to O content 2 O 3 Mass ratio of content (B 2 O 3 / Li 2O) is 5.00 or more, preferably 5.50 or more, more preferably 6.00 or more, 6.20 or more, 6.40 or more, 6.60 or more, 6.80 or more, 7.00 or more, 7.20 or more, 7.40 or more, 7.60 or more, 7.80 or more, 8.00 or more, 8.25 or more, 8.36 or more in that order. The upper limit is 21.00 or less, preferably 20.00 or less, more preferably 19.50 or less, 19.00 or less, 18.50 or less, 18.00 or less, 17.75 or less, 17.50 or less, 17.25 or less, 17.00 or less, 16.75 or less, 16.54 or less in that order. Mass ratio (B 2 O 3 / Li 2 With respect to O), the above upper limit is preferred from the viewpoint of lowering the glass transition temperature, and the above lower limit is preferred from the viewpoint of suppressing an increase in the glass transition temperature and maintaining thermal stability.
[0027] In the glass composition shown in cation percentage, Li + B relative to content 3+ Cation content ratio (B 3+ / Li + ) is preferably 1.50 or more, more preferably 2.00 or more, 2.25 or more, 2.50 or more, 2.75 or more, 3.00 or more, 3.25 or more, 3.50 or more, and 3.58 or more in that order. The upper limit is preferably 9.50 or less, more preferably 9.00 or less, 8.80 or less, 8.60 or less, 8.40 or less, 8.20 or less, 8.00 or less, 7.80 or less, 7.60 or less, 7.40 or less, 7.20 or less, and 7.10 or less in that order.
[0028] (B 3+ / Si 4+ ) In the glass composition shown in cationic percentage, Si 4+ B relative to content 3+ Cation content ratio (B 3+ / Si 4+) is preferably 1.25 or more, and more preferably 1.50 or more, 1.75 or more, 2.00 or more, 2.25 or more, 2.50 or more, 2.75 or more, 3.00 or more, 3.10 or more, 3.20 or more, 3.30 or more, 3.40 or more, and 3.50 or more in that order. In addition, the cation ratio (B 3+ / Si 4+ ) is preferably 11.00 or less, and more preferably 10.50 or less, 10.00 or less, 9.75 or less, 9.50 or less, 9.25 or less, 9.00 or less, 8.75 or less, 8.50 or less, 8.25 or less, 8.00 or less, 7.75 or less, 7.60 or less, 7.50 or less, 7.40 or less, and 7.30 or less, in that order. From the viewpoint of maintaining the thermal stability and high refractive index of the glass, the cation ratio (B 3+ / Si 4+ ) is preferably in the above range.
[0029] In the glass composition expressed in mass%, SiO 2 B relative to content 2 O 3 Mass ratio of content (B 2 O 3 / SiO 2 ) is preferably 0.25% or more, more preferably 0.50 or more, 0.75 or more, 1.00 or more, 1.20 or more, 1.40 or more, 1.60 or more, 1.70 or more, 1.80 or more, 1.90 or more, 2.00 or more, and 2.02 or more in that order. The upper limit is preferably 9.00 or less, more preferably 8.50 or less, 8.00 or less, 7.50 or less, 7.00 or less, 6.50 or less, 6.00 or less, 5.75 or less, 5.50 or less, 5.25 or less, 5.00 or less, 4.75 or less, 4.50 or less, and 4.23 or less in that order.
[0030] (SiO 2 / Li 2 O) In the glass composition shown in mass%, Li 2 SiO vs. O content 2 Mass ratio of content (SiO 2 / Li 2O) is 10.00 or less, preferably 9.00 or less, more preferably 8.50 or less, 8.00 or less, 7.50 or less, 7.00 or less, 6.75 or less, 6.50 or less, 6.25 or less, 6.00 or less, 5.75 or less, 5.50 or less, 5.25 or less, and 5.18 or less in that order. The lower limit can be more than 0, and is preferably 0.40 or more, more preferably 0.60 or more, 0.80 or more, 1.00 or more, 1.20 or more, 1.40 or more, 1.60 or more, 1.80 or more, 2.00 or more, 2.25 or more, 2.50 or more, and 2.68 or more in that order. Mass ratio (SiO 2 / Li 2 With respect to O), the above upper limit is preferred from the viewpoint of lowering the glass transition temperature, and the above lower limit is preferred from the viewpoint of suppressing an increase in the glass transition temperature and maintaining thermal stability.
[0031] In the glass composition shown in cation percentage, Li + Si content 4+ Cation ratio of content (Si 4+ / Li + ) can be 2.40 or less, and is preferably 2.30 or less, 2.20 or less, 2.10 or less, 2.00 or less, 1.90 or less, 1.80 or less, 1.70 or less, 1.65 or less, 1.60 or less, 1.55 or less, 1.50 or less, 1.48 or less, 1.46 or less, 1.44 or less, 1.42 or less, 1.40 or less, 1.38 or less, 1.36 or less, 1.34 or less, 1.32 or less, 1.30 or less, and 1.29 or less in that order. The lower limit can be more than 0, and is preferably 0.25 or more, 0.30 or more, 0.35 or more, 0.40 or more, 0.50 or more, 0.52 or more, 0.54 or more, 0.56 or more, 0.58 or more, 0.60 or more, 0.62 or more, 0.64 or more, and 0.66 or more in that order.
[0032] (Rare earth components) La 2 O 3 La 2 O 3The content, in the glass composition expressed in mass%, is 15.00% or more, and preferably 17.00% or more, and more preferably 20.00% or more, 21.00% or more, 22.00% or more, 23.00% or more, 24.00% or more, 25.00% or more, 26.00% or more, 26.50% or more, 27.00% or more, 27.50% or more, 28.00% or more, and 28.35% or more in that order. La 2 O 3 The content, in the glass composition expressed in mass%, is 55.00% or less, and preferably 50.00% or less, and more preferably 47.00% or less, 45.00% or less, 44.00% or less, 43.00% or less, 42.00% or less, 41.00% or less, 40.00% or less, 39.50% or less, 39.00% or less, 38.50% or less, 38.00% or less, 37.50% or less, and 37.22% or less in that order.
[0033] Gd 2 O 3 Gd 2 O 3 The content may be 0%, 0% or more, or more than 0% in the glass composition expressed in mass%, and is preferably 0.00% or more, 0.20% or more, 0.40% or more, 0.60% or more, and 0.80% or more in that order. The upper limit is preferably 15.00% or less, and more preferably 14.75% or less, 14.50% or less, 14.25% or less, 14.00% or less, 13.85% or less, 13.75% or less, 13.50% or less, 13.25% or less, 13.00% or less, 12.75% or less, 12.55% or less, 12.25% or less, and 12.03% or less in that order.
[0034] Y 2 O 3 Y 2 O 3The content may be 0%, 0% or more, or more than 0% in the glass composition expressed in mass %. The upper limit is preferably 11.00% or less, and more preferably 10.50% or less, 10.00% or less, 9.50% or less, 9.00% or less, 8.50% or less, 8.00% or less, 7.50% or less, 7.04% or less, 6.50% or less, 6.00% or less, and 5.84% or less in that order.
[0035] Regarding the rare earth components, La, Gd and Y are components that can increase the refractive index while maintaining low dispersion, and from the viewpoint of maintaining or improving thermal stability, the content of each rare earth oxide is preferably within the above range. Y has a smaller effect of increasing the refractive index than Gd, which is the same rare earth component. In addition, if the total content of the rare earth components is excessive, the thermal stability of the glass tends to decrease. Therefore, from the viewpoint of maintaining high refractive index characteristics while maintaining thermal stability, it is preferable to introduce La and / or Gd as the rare earth component rather than Y.
[0036] (Lu 2 O 3 / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 +Lu 2 O 3 )) From the viewpoint of maintaining thermal stability, the smaller the proportion of Lu in the total amount of rare earth components, the more preferable, and it is more preferable that Lu is not contained. From this point of view, in the glass composition expressed in mass%, 2 O 3 , Gd 2 O 3 , Y 2 O 3 and Lu 2 O 3 Lu relative to the total content 2 O 3 Mass ratio of content (Lu 2 O 3 / (La 2 O 3 +Gd 2 O 3 +Y2 O 3 +Lu 2 O 3 ) is preferably 0.50 or less, more preferably 0.40 or less, 0.30 or less, 0.20 or less, and 0.10 or less in that order. Lu 3+ It is even more preferable that the above mass ratio is zero.
[0037] (ZnO) The ZnO content, in the glass composition expressed in mass%, is 3.00% or more, preferably 3.50% or more, and more preferably in this order: 4.00% or more, 4.50% or more, 5.00% or more, 5.25% or more, 5.50% or more, 5.75% or more, 6.00% or more, 6.25% or more, 6.50% or more, 6.75% or more, 7.00% or more, 7.25% or more, 7.53% or more, 7.75% or more, 8.00% or more, 8.25% or more, 8.50% or more, 8.75% or more, 9.00% or more, 9.10% or more, 9.20% or more, and 9.30% or more. The upper limit is 30.00% or less, preferably 27.00% or less, and more preferably 25.00% or less, 23.00% or less, 22.00% or less, 21.00% or less, 20.00% or less, 19.50% or less, 19.00% or less, 18.50% or less, 17.00% or less, 16.75% or less, 16.50% or less, 16.25% or less, 16.00% or less, 15.75% or less, and 15.65% or less. Zn is a component that suppresses the decrease in refractive index, lowers the glass transition temperature, and improves meltability. On the other hand, if it is contained in a large amount, the liquidus temperature becomes high and the thermal stability of the glass decreases. From these viewpoints, the ZnO content is preferably within the above range.
[0038] (Li 2 O+ZnO) In order to achieve a low Tg, the glass composition expressed in mass% contains Li 2 The total content of O and ZnO (Li 2O+ZnO) is 10.20% or more, preferably 10.22% or more, 10.30% or more, 10.40% or more, and more preferably 10.60% or more and 10.79% or more. From the viewpoint of the thermal stability of the glass, the upper limit is preferably 21.00% or less, and more preferably 20.00% or less, 19.50% or less, 19.00% or less, 18.50% or less, 18.00% or less, 17.75% or less, 17.50% or less, 17.25% or less, 17.00% or less, and 16.79% or less.
[0039] (TiO 2 ) Ti is a component that increases the refractive index and dispersion. Moreover, excessive introduction of Ti tends to deteriorate the surface quality of the glass by reacting with the molding surface of the mold during press molding, and may also intensify the coloring of the glass. Furthermore, it is preferable that the glass does not contain Ti or that the content of Ti is small, from the viewpoint of suppressing the deterioration of the release film described below. From these viewpoints, TiO 2 The content, expressed in mass % or in the glass composition, is 0.60% or less, preferably 0.40% or less, more preferably 0.30% or less, 0.20% or less, 0.10% or less, and further preferably 0% (i.e., not contained).
[0040] (Ta 2 O 5 ) Ta is a component that maintains high refractive index, low dispersion, and thermal stability. Therefore, in the glass composition expressed in mass%, Ta 2 O 5The content is preferably 7.00% or more, more preferably 7.50% or more, 8.00% or more, 8.50% or more, 8.75% or more, 9.00% or more, 9.25% or more, 9.50% or more, 9.75% or more, 10.00% or more, 10.25% or more, and 10.43% or more in that order. The upper limit is not particularly limited, and can be, for example, 19.00% or less, preferably 18.00% or less, more preferably 17.50% or less, 17.00% or less, 16.50% or less, 16.00% or less, 15.75% or less, 15.50% or less, 15.25% or less, 15.00% or less, and 14.92% or less in that order.
[0041] (Nb 2 O 5 ) Nb is a component that acts to increase the refractive index of glass, but if contained in large amounts, it tends to reduce the thermal stability of glass. 2 O 5 The content may be 0%, 0% or more, or more than 0% in the glass composition expressed in mass%, and is preferably 0% or more, 0.10% or more, 0.20% or more, 0.30% or more, 0.40% or more, 0.50% or more, and 0.60% or more in that order. The upper limit is preferably 9.00% or less, more preferably 8.00% or less, 7.50% or less, 7.00% or less, 6.50% or less, 6.00% or less, 5.80% or less, 5.60% or less, 5.40% or less, and 5.24% or less in that order.
[0042] (ZrO 2 ) ZrO 2The content can be 0%, 0% or more, or more than 0% in the glass composition expressed by mass%, and is preferably 0.00% or more, 0.50% or more, 1.00% or more, 1.20% or more, 1.40% or more, 1.60% or more, 1.80% or more, and 1.90% or more in that order. The upper limit is preferably 10.00% or less, and more preferably 9.00% or less, 8.50% or less, 8.00% or less, 7.50% or less, 7.00% or less, 6.80% or less, 6.60% or less, 6.40% or less, 6.20% or less, 6.00% or less, and 5.90% or less in that order. By introducing Zr into the glass, the effect of improving the thermal stability of the glass without decreasing the refractive index of the glass can be obtained, so it is preferable to introduce Zr.
[0043] (WO 3 ) WO 3 The content can be 0%, 0% or more, or more than 0% in the glass composition expressed by mass%, and is preferably 0% or more, 1.00% or more, 2.00% or more, 2.50% or more, 3.00% or more, 3.50% or more, 4.00% or more, 4.20% or more, 4.40% or more, 4.60% or more, 4.80% or more, and 4.93% or more in that order. The upper limit is preferably 21.00% or less, and is preferably 20.00% or less, 19.00% or less, 18.50% or less, 18.00% or less, 17.80% or less, 17.60% or less, 17.40% or less, 17.20% or less, 17.00% or less, 16.80% or less, and 16.66% or less in that order. W is a component that improves the thermal stability and meltability of the glass and increases the refractive index. On the other hand, if it is contained in a large amount, the dispersion becomes high and the precision press suitability is reduced, so that a smaller amount is preferable.
[0044] (Nb 2 O 5 +TiO 2 +WO 3 ) / (SiO 2 +B 2 O 3 ) In the glass composition expressed in mass%, SiO 2 and B 2 O 3 Nb content relative to the total content of2 O 5 , TiO 2 and W.O. 3 Mass ratio of the total content of Nb 2 O 5 +TiO 2 +WO 3 ) / (SiO 2 +B 2 O 3 ) is preferably 0.40 or more, more preferably 0.45 or more, 0.50 or more, 0.56 or more, 0.57 or more, 0.58 or more, 0.59 or more, 0.60 or more, 0.61 or more, 0.62 or more, and 0.63 or more in that order. The upper limit is preferably 1.60 or less, more preferably 1.40 or less, 1.35 or less, 1.30 or less, 1.28 or less, 1.26 or less, 1.24 or less, 1.22 or less, 1.20 or less, 1.19 or less, 1.18 or less, 1.17 or less, 1.16 or less, 1.15 or less, and 1.14 or less in that order. Mass ratio (Nb 2 O 5 +TiO 2 +WO 3 ) / (SiO 2 +B 2 O 3 ) is preferably at the above lower limit in view of maintaining the high refractive index characteristics of the glass, and is preferably at the above upper limit in view of maintaining the thermal stability.
[0045] (ZnO / WO 3 ) In the glass composition shown in mass%, WO 3 Mass ratio of ZnO content to WO 3 ) is preferably 0.10 or more, more preferably 0.20 or more, 0.30 or more, 0.40 or more, 0.50 or more, 0.60 or more, 0.63 or more, 0.67 or more, 0.70 or more, 0.73 or more, and 0.76 or more in that order. The upper limit is preferably 5.00 or less, more preferably 4.80 or less, 4.60 or less, 4.40 or less, 4.20 or less, 4.00 or less, 3.80 or less, 3.60 or less, 3.40 or less, 3.20 or less, 3.00 or less, 2.80 or less, 2.60 or less, and 2.46 or less in that order. Mass ratio (ZnO / WO 3) is preferably at the above lower limit from the viewpoint of lowering the glass transition temperature and maintaining low dispersion, and is preferably at the above upper limit from the viewpoint of maintaining the high refractive index characteristics of the glass.
[0046] (Sb 2 O 3 ) Sb is a component that functions as a clarifier. The smaller the amount of Sb added, the more preferable it is from the viewpoints of suppressing damage to the molding surface of the press mold during precision press molding and suppressing coloring of the glass. 2 O 3 The content is Sb in the glass composition expressed as mass%. 2 O 3 Content (Sb 2 O 3 Sb when the total mass of glass components other than Sb is 100 mass% 2 O 3 The content is preferably 0% or more, 0.01% or more, and 0.02% or more, in that order, and more preferably 1.00% or less, 0.90% or less, 0.80% or less, 0.70% or less, 0.60% or less, and 0.50% or less, in that order.
[0047] (anion component) The optical glass may be an oxide glass, and may contain, as an anion component, O 2- In the present invention and this specification, the content of an anion component in a glass composition expressed in anion % is expressed in anion %. Here, "anion %" is a value calculated by "(number of anions of interest / total number of anions in glass components) x 100", and means the molar percentage of the amount of anion of interest relative to the total amount of anion components. In a glass composition expressed in anion %, O 2- The content is preferably 95.0 anion % or more, more preferably 97.0 anion % or more, 98.0 anion % or more, 99.0 anion % or more, 99.5 anion % or more, and 100 anion % in that order. -The content is preferably 0.1 anion % or less, and more preferably 0 anion % (i.e., no F). A composition expressed in mass % on an oxide basis as a result of quantitative analysis of the glass composition can be converted to a glass composition expressed in anion % by, for example, the method described above for converting to a glass composition expressed in cation %.
[0048] <Glass properties> (glass transition temperature Tg) The optical glass can have a low glass transition temperature Tg by having the above glass composition. Low Tg glass is preferable, for example, from the viewpoint of suppressing deterioration of the release film and suppressing wear of the press molding die in precision press molding. The Tg of the optical glass is less than 610°C, and is preferably 608°C or less, 606°C or less, 604°C or less, 602°C or less, 600°C or less, 598°C or less, 596°C or less, 594°C or less, 592°C or less, and 590°C or less in this order. The lower limit of Tg is not particularly limited, and can be, for example, 530°C or more, and is preferably 540°C or more, 550°C or more, 555°C or more, 560°C or more, 565°C or more, and 570°C or more in this order. The glass transition temperature Tg is determined by the method described below.
[0049] (Formula (1)) In the above optical glass, the refractive index nd and the glass transition temperature Tg satisfy the following formula (1). Formula (1): Tg<2500*nd-4050 By satisfying formula (1), the above optical glass can achieve both high refractive index properties and press moldability. In general, the higher the refractive index, the higher the Tg tends to be. In contrast, formula (1) indicates that the refractive index is high but the Tg is low. The above optical glass preferably satisfies the following formula (1-1), more preferably satisfies the following formula (1-2), even more preferably satisfies the following formula (1-3), still more preferably satisfies the following formula (1-4), and even more preferably satisfies the following formula (1-5). Formula (1-1): Tg<2500*nd-4060 Formula (1-2): Tg<2500*nd-4070 Formula (1-3): Tg<2500*nd-4080 Formula (1-4): Tg<2500*nd-4090 Formula (1-5): Tg<2500*nd-4100
[0050] (Formula (2)) In the above optical glass, the refractive index nd and the Abbe number vd satisfy the following formula (2). Formula (2): νd>-88.355*nd+201 An optical glass satisfying the above formula (2) exhibits low dispersion at a given refractive index and is useful as a material for optical elements.
[0051] (Refractive index nd) As long as the above formula (1) and formula (2) are satisfied, the refractive index nd of the optical glass is not particularly limited. Since high refractive index glass is useful as a material for optical elements, the refractive index nd of the optical glass is preferably 1.8600 or more, more preferably 1.8620 or more, 1.8640 or more, 1.8660 or more, 1.8680 or more, 1.8700 or more, 1.8720 or more, 1.8740 or more, and 1.8760 or more in this order. The upper limit is preferably 1.9000 or less, more preferably 1.8980 or less, 1.8960 or less, 1.8940 or less, 1.8920 or less, 1.8900 or less, 1.8880 or less, and 1.8860 or less in this order.
[0052] (Abbe number νd) As long as the above formula (2) is satisfied, the Abbe number vd of the optical glass is not particularly limited. Since glass exhibiting low dispersion is useful as a material for optical elements, the Abbe number vd of the optical glass is preferably 34.0 or more, and more preferably 34.20 or more, 34.40 or more, 34.60 or more, 34.80 or more, 35.00 or more, 35.10 or more, 35.20 or more, 35.30 or more, 35.40 or more, 35.50 or more, 35.60 or more, 35.70 or more, 35.80 or more, 35.90 or more, 36.00 or more, 36.10 or more, and 36.20 or more in that order. The upper limit is preferably 40.0 or less, and more preferably 39.50 or less, 39.00 or less, 38.80 or less, 38.60 or less, 38.40 or less, 38.20 or less, 38.00 or less, 37.90 or less, 37.80 or less, and 37.76 or less, in that order. When glass is considered as a material for optical elements, increasing the refractive index of glass corresponds to expanding the degree of freedom of glass. Increasing the refractive index is preferable from the viewpoint of expanding the degree of freedom. On the other hand, if the refractive index is increased while maintaining the dispersion, the glass stability may tend to decrease. From these viewpoints, the Abbe number νd is preferably in the above-mentioned range.
[0053] (Liquidus temperature LT) As described above, the optical glass does not contain Ti or contains a small amount of Ti. The optical glass does not contain Ti or contains a small amount of Ti and has a glass composition that realizes the desired Tg and optical constants described above, and has a liquidus temperature LT of 1090°C or higher. The liquidus temperature LT can be 1100°C or higher, 1110°C or higher, or 1120°C or higher. From the viewpoint of maintaining viscosity during molding, the upper limit is preferably 1230°C or lower, and more preferably 1220°C or lower, 1210°C or lower, 1200°C or lower, 1190°C or lower, and 1180°C or lower in that order.
[0054] In the present invention and this specification, the liquidus temperature LT is determined by the following method. 5-8cc of glass is placed in a platinum crucible and heated for 2 hours in a furnace with the furnace atmosphere temperature T until it becomes molten, after which it is removed from the furnace and left at room temperature to cool to room temperature. Room temperature should be in the range of 20℃-30℃. The presence or absence of crystal precipitation in the cooled glass is determined by observation under an optical microscope (100x magnification). The presence or absence of crystal precipitation is determined for each different T (in 10°C increments) using the above method. The lowest temperature T at which no crystal precipitation is observed is taken as the liquidus temperature.
[0055] (specific gravity) It is preferable that the specific gravity of the optical glass is low from the viewpoint of reducing the weight of the optical element. The specific gravity of the optical glass is, for example, preferably 5.75 g / cc or less, more preferably 5.70 g / cc or less, 5.65 g / cc or less, and 5.58 g / cc or less in that order. The specific gravity of the optical glass can be, for example, 5.10 g / cc or more, but the lower limit is not particularly limited because the lower the specific gravity, the more preferable it is. In the present invention and this specification, the specific gravity is a value measured by Archimedes' method.
[0056] (Coloring degree λ 5 , λ 70 , λ 80 ) The light transmittance of the glass, specifically, the suppression of the shift of the light absorption edge on the short wavelength side to longer wavelengths, is the coloring degree λ 5 , λ 70 and λ 80 The coloring degree λ can be evaluated by one or more of the following: 5 λ represents the wavelength at which the spectral transmittance (including surface reflection loss) of a 10 mm thick glass is 5% from the ultraviolet to visible range. 70 is λ 5 λ represents the wavelength at which the spectral transmittance measured by the method described above is 70%. 80 is λ 5 The wavelengths at which the spectral transmittance measured by the method described above is 80% are shown in the table below. 5 , λ 70 and λ 80is a value measured in the wavelength range of 250 to 700 nm. The spectral transmittance T (%) of glass in the present invention and this specification is calculated by dividing the intensity of light incident perpendicularly on one of two optically polished parallel planes of a glass sample by the intensity of light I in The intensity of the light that passes through the glass sample and exits from the other side is I out When T(%)=I out / I in ×100 It is expressed as: Coloring degree λ 5 , λ 70 and λ 80 According to this method, the absorption edge on the short wavelength side of the spectral transmittance can be quantitatively evaluated. When bonding lenses together with an ultraviolet-curable adhesive to produce a cemented lens, the adhesive is cured by irradiating it with ultraviolet light through an optical element. From the viewpoint of efficiently curing the ultraviolet-curable adhesive, it is preferable that the absorption edge on the short wavelength side of the spectral transmittance is in a short wavelength range. As an index for quantitatively evaluating the absorption edge on the short wavelength side, the coloring degree λ 5 , λ 70 and λ 80 One or more of the following may be used. The optical glass preferably has a λ of 380 nm or less. 5 It can be shown that λ 5 is more preferably 370 nm or less, 360 nm or less, and 350 nm or less, in that order. 5 The shorter the wavelength, the more preferable it is, and the lower limit is not particularly limited. The optical glass preferably has a λ of 430 nm or less. 70 It can be shown that λ 70 is more preferably 420 nm or less, 410 nm or less, 400 nm or less, and 395 nm or less, in that order. 70 The shorter the wavelength, the more preferable it is, and the lower limit is not particularly limited. The optical glass preferably has a λ of 510 nm or less. 80 It can be shown that λ 80 is more preferably 500 nm or less, 490 nm or less, 480 nm or less, and 470 nm or less, in that order.80 The shorter the wavelength, the more preferable it is, and the lower limit is not particularly limited.
[0057] <Glass manufacturing method> The optical glass can be obtained by weighing, preparing and thoroughly mixing raw materials such as oxides, carbonates, sulfates, nitrates and hydroxides so as to obtain the desired glass composition, heating and melting the mixture in a melting vessel, degassing and stirring the mixture to produce a homogeneous, bubble-free molten glass, and then molding the glass. Specifically, the glass can be produced by using a known melting method.
[0058] [Glass material for press molding, its manufacturing method, and manufacturing method of glass molded body] According to one aspect of the present invention, there are provided a glass material for press molding made of the above-mentioned optical glass, a glass molded article made of the above-mentioned optical glass, and methods for producing them. The glass material for press molding means a glass lump that is heated and subjected to press molding. Examples of glass materials for press molding include glass blocks having a mass equivalent to the mass of press-molded products such as precision press molding preforms and glass materials (glass gobs for press molding) for press molding optical element blanks. The press molding glass material can be produced through a process of processing a glass molded body. The glass molded body can be produced by heating and melting a glass raw material as described above, and molding the resulting molten glass. Examples of the processing method of the glass molded body include cutting, grinding, polishing, etc.
[0059] [Optical element blank and its manufacturing method] According to one aspect of the present invention, an optical element blank made of the above optical glass can be provided. The optical element blank is a glass molded body having a shape similar to that of the optical element to be manufactured. The optical element blank can be produced by a method of molding glass into a shape obtained by adding a processing allowance to be removed by processing to the shape of the optical element to be manufactured. For example, the optical element blank can be produced by a method of heating and softening a glass material for press molding and press molding it (reheat press method), or a method of supplying a molten glass lump to a press mold by a known method and press molding it (direct press method).
[0060] [Optical elements and their manufacturing methods] According to one aspect of the present invention, an optical element made of the above optical glass can be provided. Examples of the types of optical elements include lenses such as spherical lenses and aspherical lenses, prisms, and diffraction gratings. Examples of the lens shapes include biconvex lenses, plano-convex lenses, biconcave lenses, plano-concave lenses, convex meniscus lenses, and concave meniscus lenses.
[0061] As one embodiment of the method for producing an optical element, a method for producing an optical element by heating a preform for precision press molding and performing precision press molding can be mentioned. A known press mold can be used for precision press molding, and a known molding method can be applied. The method for producing an optical element by precision press molding is suitable for producing aspherical lenses, microlenses, diffraction gratings, etc.
[0062] It is preferable to coat the surface of the precision press molding preform with a mold release film in order to prevent the glass from fusing with the press mold surface during precision press molding while allowing the glass to stretch well along the molding surface. Such mold release films are known. The optical glass is a low Tg glass having a glass transition temperature in the range described above, and does not contain Ti or contains a small amount of Ti. A precision press molding preform made of such glass is preferable from the viewpoint of suppressing deterioration of the mold release film. An example of the mold release film is a carbon-containing film. The carbon-containing film can be, for example, a film containing carbon as the main component (when the element content in the film is expressed in atomic %, the carbon content is higher than the content of other elements). The carbon-containing film can be formed by known methods such as vacuum deposition, sputtering, and ion plating using a carbon raw material, and known methods such as pyrolysis using a material gas such as hydrocarbon.
[0063] A schematic cross-sectional view of a precision press molding apparatus is shown in Figure 1. Precision press molding can be carried out, for example, as follows. After placing a precision press molding preform (hereinafter simply referred to as "preform") 4 between a lower die 2 and an upper die 1 that constitute a press molding die, a nitrogen atmosphere is created inside the quartz tube 11, and electricity is passed through a heater (not shown) to heat the inside of the quartz tube 11. The temperature inside the press molding die is raised to, for example, 10 6 ~10 10 The temperature is set to a temperature at which the viscosity of the glass is 10 dPa·s, and while maintaining the same temperature, the push rod 13 is lowered to push the upper die 1 and press the preform set in the mold. After pressing, the pressure of the press is released, and while the pressed glass molded product is still in contact with the lower die 2 and the upper die 1, the viscosity of the glass is adjusted to, for example, 10 12The glass molded product is slowly cooled to a temperature of at least dPa·s, and then rapidly cooled to room temperature, and removed from the mold. In this manner, an optical element can be obtained. In Fig. 1, a holding member 10 holds the lower die 2 and the body die 3, and a support rod 9 supports the upper die 1, lower die 2, body die 3, and holding member 10, while receiving the pressing pressure from a pressing rod 13. A thermocouple 14 is inserted inside the lower die 2 to monitor the temperature inside the press mold.
[0064] Another embodiment of the method for producing an optical element is a method for producing an optical element by machining an optical element blank. Examples of the machining include cutting, milling, rough grinding, fine grinding, polishing, etc. This manufacturing method is suitable for producing spherical lenses, prisms, etc. EXAMPLES
[0065] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the embodiments shown in the examples.
[0066] [Examples No. 1 to No. 197] To obtain the glass composition shown in the table below, the corresponding phosphate, fluoride, nitrate, sulfate, carbonate, hydroxide, oxide, boric acid, etc. were used as raw materials for introducing each component, and the raw materials were weighed and thoroughly mixed to prepare a blended raw material. In the table below, "cat%" stands for "cation %, "wt%" stands for "mass %, "mol%" stands for "mol %, and Sb 2 O 3 The content is expressed as a percentage. For example, "B 3+ / Si 4+ "(cat%)" is the Si content in the glass composition expressed as cation percentage. 4+ B relative to content 3+ The cation ratio of the content is shown, and "B 2 O 3 / SiO 2 (wt%)" is the SiO content in the glass composition expressed as mass%. 2 B relative to content 2 O 3The above also applies to the notations of various cation ratios and various mass ratios in the following tables. The raw materials were placed in a platinum crucible and heated in a furnace set at 1250-1350°C for 120 minutes. The molten glass was stirred to homogenize it, then poured into a preheated mold and allowed to cool to near the glass transition temperature. It was then immediately placed in an annealing furnace and held at about the glass transition temperature for about 30 minutes, then slowly cooled at a rate of -30°C / hour for 4 hours, and then allowed to cool to room temperature in the furnace to obtain the optical glasses of Examples No. 1 to No. 197 shown in the table below. The anion components of the optical glasses shown in the table below are O 2- The content is 100% anion.
[0067] <Physical property evaluation> The physical properties of each optical glass shown in the following table were measured by the following methods.
[0068] (1) Refractive index nd Abbe number νd The refractive index nd and Abbe number vd of each optical glass were measured by the refractive index measurement method specified by the Japan Optical Glass Industry Association. The following table shows the calculated value of the right side of formula (1) and the calculated value of the right side of formula (2) for each optical glass. If each formula is satisfied, the "Judgment" column is marked with "◯".
[0069] (2) Glass transition temperature Tg The glass was thoroughly crushed in a mortar and used as a sample. A platinum cell was used as a sample container, and the glass transition temperature Tg was measured at a heating rate of 10°C / min using a differential scanning calorimeter (DSC3300SA) manufactured by NETZSCH JAPAN.
[0070] (3) Specific gravity Specific gravity was measured by Archimedes' method.
[0071] (4) Liquidus temperature LT The liquidus temperature LT was measured by the method described above.
[0072] (4) Coloring degree λ5 , λ 70 , λ 80 A glass sample having a thickness of 10±0.1 mm and two optically polished flat surfaces facing each other was used to measure the spectral transmittance T (%) using a spectrophotometer. The wavelength (nm) at which T becomes 5% is defined as λ 5 Let λ be the wavelength (nm) at which T is 70%. 70 Let λ be the wavelength (nm) at which T is 80%. 80 It was decided.
[0073] The results are shown in the table below.
[0074] [Table 2-1]
[0075] [Table 2-2]
[0076] [Table 2-3]
[0077] [Table 2-4]
[0078] [Table 2-5]
[0079] [Table 2-6]
[0080] [Table 2-7]
[0081]
Table 2-8
[0082]
Table 2-9
[0083]
Table 2-10
[0084]
Table 2-11
[0085]
Table 2-12
[0086]
Table 2-13
[0087]
Table 3-1
[0088]
Table 3-2
[0089]
Table 3-3
[0090]
Table 3-4
[0091]
Table 3-5
[0092]
Table 3-6
[0093]
Table 3-7
[0094]
Table 3-8
[0095]
Table 3-9
[0096]
Table 3-10
[0097]
Table 3-11
[0098]
Table 3-12
[0099]
Table 3-13
[0100]
Table 4-1
[0101]
Table 4-2
[0102]
Table 4-3
[0103]
Table 4-4
[0104]
Table 4-5
[0105]
Table 4-6
[0106]
Table 4-7
[0107]
Table 4-8
[0108]
Table 4-9
[0109]
Table 4-10
[0110]
Table 4-11
[0111]
Table 4-12
[0112] [Table 4-13]
[0113] [Preparation of preforms for precision press molding] For each of the above examples, the corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. were used as raw materials for introducing each component so as to obtain the glass composition shown in the above table, and the raw materials were weighed and thoroughly mixed to obtain a blended raw material. As Comparative Example 1, a raw material was prepared by weighing and thoroughly mixing the raw materials used to introduce each component, such as corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc., so as to obtain the glass composition of Example 10 shown in Table 1 of Patent Document 1 (JP 2008-201661 A). As Comparative Example 2, a raw material was prepared by weighing and thoroughly mixing the raw materials used to introduce each component, such as corresponding nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc., so as to obtain the glass composition of Example 34 shown in Table 1 of Patent Document 1 (JP 2008-201661 A). One example of preform production (Production Example 1) will be described. The mixed raw materials were placed in a platinum crucible, and heated and melted. The clarified and homogenized molten glass was allowed to flow at a constant rate from a platinum alloy pipe, the temperature of which was adjusted to a temperature range that allowed stable flow without devitrification of the glass, and separated into molten glass lumps of the desired preform mass by a dropping or drop cutting method. The separated molten glass lumps were received in a mold with a gas nozzle at the bottom, and gas was ejected from the gas nozzle to float the glass lumps, forming a preform for precision press molding. A flattened spherical preform was obtained by adjusting and setting the separation interval of the molten glass lumps. Another example of preform production (production example 2) is a method in which a homogeneous molten glass obtained by melting a blend of raw materials is poured into a mold and molded, distortion in the resulting molded body is removed by annealing, the molded body is cut or fractured to divide it into pieces of specified dimensions and shapes to produce a plurality of glass pieces, and the glass pieces are polished to smooth their surfaces and formed into a preform made of glass of a specified mass. For the above-mentioned Examples and Comparative Examples, preforms for precision press molding were produced according to Production Example 2.
[0114] [Experiment to evaluate deterioration of release film] For each of the above-mentioned examples and comparative examples, the surface of the prepared preform was coated with a carbon-containing film and heated in a nitrogen atmosphere. Specifically, after the inside of the furnace was evacuated, nitrogen was introduced to a pressure of about 0.2 MPa, and the glass was heated to 2.5 10 The mixture was heated for 360 seconds at a temperature that would result in a viscosity of about poise. The temperature was increased from room temperature at a rate of 25°C / min and decreased at a rate of 20°C / min. After the above heating, whether or not a carbon-containing film remained on the surface of each preform was evaluated by measuring the preform surface with a SEM-EDX (Scanning Electron Microscope-Energy Dispersive X-ray Spectrometry) at an acceleration voltage of 3 to 25 kV to confirm the presence or absence of carbon. As a result of the above experiments, it was confirmed that a carbon-containing film remained on the surface of the preform in all of the above examples. In contrast, it was confirmed that no carbon-containing film remained on the surface of the preform in Comparative Example 1 and Comparative Example 2. The glass constituting the preform in Comparative Example 1 contained TiO in the glass composition expressed in mass %. 2 The glass content was 0.83 mass % (see Table 1 in Patent Document 1 (JP 2008-201661 A)). The glass transition temperature of the glass constituting the preform of Comparative Example 2 was 610° C. (see Table 1 in Patent Document 1 (JP 2008-201661 A)). From the above results, as in the above example, TiO 2It can be confirmed that the glass having a content of 0.6 mass % or less and a glass transition temperature of less than 610° C. can prevent the deterioration of the release film.
[0115] In order to confirm the correlation between the above experiments and precision press suitability, the surfaces of the preforms produced in the above examples and comparative examples were coated with a carbon-containing film and introduced into a press molding die including upper and lower dies and a body die made of SiC with carbon-containing release films provided on the molding surfaces. The mold and preform were heated together in a nitrogen atmosphere to soften the preform, and precision press molding was performed to produce an aspheric biconvex lens with a diameter of 30 mm and a thickness of 4 mm in the optical axis direction. When precision pressing was performed in the above-mentioned Examples, no deterioration of the mold release film was observed even after more than 150 shots, and mass productivity was good. In contrast, when precision pressing was performed for 100 shots in the above-mentioned Comparative Example, deterioration of the mold release film was significant, resulting in damage to the molding die and defects in the lens shape and appearance, and poor mass productivity. From the above results, it was confirmed that the glass of the above embodiment can provide excellent mass productivity in precision pressing. Furthermore, the glass of the above embodiment can be used to manufacture large-diameter lenses exceeding φ30 mm, lenses with a thickness in the optical axis direction exceeding 4 mm (more preferably lenses with a maximum thickness exceeding 5 mm), lenses with complex shapes, and the like with high mass productivity.
[0116] Finally, the above-mentioned aspects will be summarized.
[0117] [1] In the glass composition expressed in mass%, Li 2 O content exceeds 0% by mass, B 2 O 3 The content is 3.00% by mass or more and 30.00% by mass or less, SiO 2 The content is more than 0% by mass and 8.00% by mass or less, La 2 O 3 The content is 15.00% by mass or more and 55.00% by mass or less, ZnO content is 3.00% by mass or more and 30.00% by mass or less, TiO 2 Content is 0.60% by mass or less, Li 2 The total content of O and ZnO (Li 2 O + ZnO) is 10.20 mass% or more, Li 2 B relative to O content 2 O 3 Mass ratio of content (B 2 O 3 / Li 2 O) is between 5.00 and 21.00, Li 2 SiO vs. O content 2 Mass ratio of content (SiO 2 / Li 2 O) is 10.00 or less, and Glass transition temperature Tg is less than 610℃, Liquidus temperature LT is 1090℃ or higher, An optical glass having a refractive index nd and a glass transition temperature Tg that satisfy the following formula (1), and a refractive index nd and an Abbe number vd that satisfy the following formula (2). Formula (1): Tg<2500*nd-4050 Formula (2): νd>-88.355*nd+201 [2] In the glass composition expressed in cation percentage, Si 4+ B relative to content 3+ Cation content ratio (B 3+ / Si 4+ ) is 1.25 or more and 11.00 or less. [3] In the glass composition expressed in mass%, SiO 2 and B 2 O 3 Nb content relative to the total content of 2 O 5 , TiO 2 and W.O. 3 Mass ratio of the total content of Nb 2 O 5 +TiO 2 +WO 3 ) / (SiO 2 +B 2 O 3) is 0.40 or more and 1.60 or less. [4] In the glass composition expressed in mass%, WO 3 Mass ratio of ZnO content to WO 3 ) is 0.10 or more and 5.00 or less. [5] In the glass composition shown in mass%, La 2 O 3 , Gd 2 O 3 , Y 2 O 3 and Lu 2 O 3 Lu relative to the total content 2 O 3 Mass ratio of content (Lu 2 O 3 / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 +Lu 2 O 3 )) is 0.50 or less. [6] In the glass composition shown in cation percentage, Li + The optical glass according to any one of [1] to [5], having a cationic content of 0.50 cation % or more. [7] The optical glass according to any one of [1] to [6], which has a refractive index nd of 1.8600 or more. [8] The optical glass according to any one of [1] to [7], having an Abbe number vd of 34.0 or more and 40.0 or less. [9] In the glass composition expressed in mass%, SiO 2 and B 2 O 3 Nb content relative to the total content of 2 O 5 , TiO 2 and W.O. 3 Mass ratio of the total content of Nb 2 O 5 +TiO 2 +WO 3) / (SiO 2 +B 2 O 3 ) is 0.40 or more and 1.60 or less, WO 3 Mass ratio of ZnO content to WO 3 ) is 0.10 or more and 5.00 or less, La 2 O 3 , Gd 2 O 3 , Y 2 O 3 and Lu 2 O 3 Lu relative to the total content 2 O 3 Mass ratio of content (Lu 2 O 3 / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 +Lu 2 O 3 )) is 0.50 or less, In the glass composition expressed as cation percentage, S 4+ B relative to content 3+ Cation content ratio (B 3+ / Si 4+ ) is between 1.25 and 11.00, Li + The content is 0.50 cation% or more, The refractive index nd is 1.8600 or more, and 2. The optical glass according to claim 1, having an Abbe number vd of 34.0 or greater and 40.0 or less.
[10] An optical element comprising the optical glass according to any one of [1] to [9].
[0118] The embodiments disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. For example, by subjecting the above-mentioned exemplary glass compositions to compositional adjustments as described in the specification, an optical glass according to one aspect of the present invention can be obtained. Furthermore, it is of course possible to arbitrarily combine two or more of the items described in the specification as examples or preferred ranges.
Claims
1. In the glass composition expressed in mass%, Li 2 O content 0 mass% over, B 2 O 3 The content is 3.00 mass% or more and 30.00 mass% or less, SiO 2 The content is more than 8.00% by mass or less, La 2 O 3 The content is 15.00% by mass or more and 55.00% by mass or less, ZnO content is 3.00% by mass or more and 30.00% by mass or less, TiO 2 The content is 0.60% by mass or less, Li 2 The total content of O and ZnO (Li 2 O + ZnO) is 10.20 mass% or more, Li 2 B vs. O content 2 O 3 Mass ratio of content (B 2 O 3 / Li 2 O) is 5.00 or more and 21.00 or less, Li 2 SiO vs. O content 2 Mass ratio of content (SiO 2 / Li 2 O) is 10.00 or less, In the glass composition expressed in mass%, the mass ratio of the total content of Nb 2 O 5 , TiO 2 and WO 3 to the total content of SiO 2 and B 2 O 3 (Nb 2 O 5 + TiO 2 + WO 3 ) / (SiO 2 + B 2 O 3 ) is 0.56 or more and 1.60 or less; and A glass transition temperature Tg of less than 610° C. The liquidus temperature LT is 1090°C or higher, An optical glass having a refractive index nd and a glass transition temperature Tg that satisfy the following formula (1), and a refractive index nd and an Abbe number vd that satisfy the following formula (2). Formula (1): Tg<2500*nd-4050 Formula (2): νd>-88.355*nd+201
2. A glass composition expressed in mass percent, Li 2 O content is more than 0% by mass, B 2 O 3 content is 3.00% by mass or more and 30.00% by mass or less, SiO 2 content is more than 0% by mass and not more than 8.00% by mass, The La 2 O 3 content is 15.00 mass% or more and 55.00 mass% or less, ZnO content is 3.00% by mass or more and 30.00% by mass or less, The TiO 2 content is 0.60 mass% or less, The total content of Li 2 O and ZnO (Li 2 O + ZnO) is 10.20 mass% or more; a mass ratio (B 2 O 3 / Li 2 O) of the B 2 O 3 content to the Li 2 O content is 5.00 or more and 21.00 or less; a mass ratio of the SiO 2 content to the Li 2 O content (SiO 2 / Li 2 O) of 10.00 or less; In the glass composition expressed in mass%, the mass ratio of the ZnO content to the WO 3 content (ZnO / WO 3 ) is 0.10 or more and 2.46 or less; and A glass transition temperature Tg of less than 610° C. The liquidus temperature LT is 1090°C or higher, An optical glass having a refractive index nd and a glass transition temperature Tg that satisfy the following formula (1), and a refractive index nd and an Abbe number vd that satisfy the following formula (2). Formula (1): Tg<2500*nd-4050 Formula (2): νd>-88.355*nd+201
3. A glass composition expressed in mass percent, Li 2 O content is more than 0% by mass, B 2 O 3 content is 3.00% by mass or more and 30.00% by mass or less, SiO 2 content is more than 0% by mass and not more than 8.00% by mass, The La 2 O 3 content is 15.00 mass% or more and 55.00 mass% or less, ZnO content is 3.00% by mass or more and 30.00% by mass or less, The TiO 2 content is 0.60 mass% or less, The WO 3 content is 7.27 mass% or more; The total content of Li 2 O and ZnO (Li 2 O + ZnO) is 10.20 mass% or more; a mass ratio (B 2 O 3 / Li 2 O) of the B 2 O 3 content to the Li 2 O content is 5.00 or more and 21.00 or less; a mass ratio of the SiO 2 content to the Li 2 O content (SiO 2 / Li 2 O) of 10.00 or less; In the glass composition expressed in mass%, the mass ratio of the total content of Nb 2 O 5 , TiO 2 and WO 3 to the total content of SiO 2 and B 2 O 3 (Nb 2 O 5 + TiO 2 + WO 3 ) / (SiO 2 + B 2 O 3 ) is 0.40 or more and 1.60 or less; and A glass transition temperature Tg of less than 610° C. The liquidus temperature LT is 1090°C or higher, An optical glass having a refractive index nd and a glass transition temperature Tg that satisfy the following formula (1), and a refractive index nd and an Abbe number vd that satisfy the following formula (2). Formula (1): Tg<2500*nd-4050 Formula (2): νd>-88.355*nd+201
4. A glass composition expressed in mass percent, Li 2 O content is more than 0% by mass, B 2 O 3 content is 3.00% by mass or more and 30.00% by mass or less, SiO 2 content is more than 0% by mass and not more than 8.00% by mass, The La 2 O 3 content is 15.00 mass% or more and 55.00 mass% or less, ZnO content is 3.00% by mass or more and 30.00% by mass or less, The TiO 2 content is 0.60 mass% or less, The WO 3 content is 7.27 mass% or more; The total content of Li 2 O and ZnO (Li 2 O + ZnO) is 10.20 mass% or more; a mass ratio (B 2 O 3 / Li 2 O) of the B 2 O 3 content to the Li 2 O content is 5.00 or more and 21.00 or less; a mass ratio of the SiO 2 content to the Li 2 O content (SiO 2 / Li 2 O) of 10.00 or less; In the glass composition expressed in mass%, the mass ratio of the ZnO content to the WO 3 content (ZnO / WO 3 ) is 0.10 or more and 5.00 or less; and A glass transition temperature Tg of less than 610° C. The liquidus temperature LT is 1090°C or higher, An optical glass having a refractive index nd and a glass transition temperature Tg that satisfy the following formula (1), and a refractive index nd and an Abbe number vd that satisfy the following formula (2). Formula (1): Tg<2500*nd-4050 Formula (2): νd>-88.355*nd+201
5. In the glass composition expressed in cation percentage, Si 4+ B relative to content 3+ The cationic ratio of the content (B 3+ / Si 4+ 5. The optical glass according to claim 1, wherein the refractive index is 1.25 or more and 11.00 or less.
6. In the glass composition expressed in mass%, La 2 O 3 , Gd 2 O 3 , Y 2 O 3 and Lu 2 O 3 Lu relative to the total content 2 O 3 Mass ratio of content (Lu 2 O 3 / (La 2 O 3 +Gd 2 O 3 +Y 2 O 3 +Lu 2 O 3 5. The optical glass according to claim 1, wherein the refractive index is 0.50 or less.
7. In the glass composition shown in cationic percentage, Li + 5. The optical glass according to claim 1, wherein the content is at least 0.50 cation %.
8. 5. The optical glass according to claim 1, which has a refractive index nd of 1.8600 or more.
9. 5. The optical glass according to claim 1, wherein the Abbe number vd is 34.0 or more and 40.0 or less.
10. An optical element comprising the optical glass according to any one of claims 1 to 4.
Citation Information
Patent Citations
Optical glass, preform for precision press-molding, optical element, and methods for manufacturing the same
JP2008201661A
Optical glass for mold press molding
JP2009102215A
Optical glass for mold press forming
JP2009173520A
Optical glass
JP2013256438A
Optical glass, glass base material and optical element
JP2018052800A